2023
DOI: 10.1021/jacs.2c12431
|View full text |Cite
|
Sign up to set email alerts
|

Doping Shortens the Metal/Metal Distance and Promotes OH Coverage in Non-Noble Acidic Oxygen Evolution Reaction Catalysts

Abstract: Acidic water electrolysis enables the production of hydrogen for use as a chemical and as a fuel. The acidic environment hinders water electrolysis on non-noble catalysts, a result of the sluggish kinetics associated with the adsorbate evolution mechanism, reliant as it is on four concerted proton-electron transfer steps. Enabling a faster mechanism with non-noble catalysts will help to further advance acidic water electrolysis. Here, we report evidence that doping Ba cations into a Co3O4 framework to form Co3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(66 citation statements)
references
References 37 publications
2
64
0
Order By: Relevance
“…These results demonstrate that C@CeO 2 /Co 3 O 4 induces faster rates of electron and ion transport, both of which favor the water molecule dissociation and intermediate transport (*H 2 O, *OH, etc.) at the interface . In summary, it can be deduced that C@CeO 2 /Co 3 O 4 accelerates the reaction kinetic process compared to Co 3 O 4 , C/Co 3 O 4 , and CeO 2 /Co 3 O 4 .…”
Section: Resultsmentioning
confidence: 82%
“…These results demonstrate that C@CeO 2 /Co 3 O 4 induces faster rates of electron and ion transport, both of which favor the water molecule dissociation and intermediate transport (*H 2 O, *OH, etc.) at the interface . In summary, it can be deduced that C@CeO 2 /Co 3 O 4 accelerates the reaction kinetic process compared to Co 3 O 4 , C/Co 3 O 4 , and CeO 2 /Co 3 O 4 .…”
Section: Resultsmentioning
confidence: 82%
“…, 1.76 and 1.86 V vs RHE) for the Co 3 O 4 . This is not surprising since the 18 O isotope-labeled DEMS experiment has previously demonstrated that Co 3 O 4 spinel can realize the diatomic O–O radical coupling in acid …”
Section: Resultsmentioning
confidence: 86%
“…This indicates that the OER over the RuCoO x could possibly proceed with an unusual DOM reaction pathway driven by the heteroatomic Ru oct –O–Co oct units. The DOM involves the adsorption of the *OH intermediate, the subsequent dehydrogenation, and the final dioxygen radical coupling process (Figure c), which has been widely studied in theoretical and experimental aspects. We then further calculated the bond lengths and the bond angles of the Ru oct –O–Co oct units and found that they are highly symmetrical (Figure e) along with shortened atomic distances (Figure g). Both are beneficial to conducting the final O–O radical coupling with a low thermodynamic energy barrier. ,, Indeed, our simulation shows that the required free energy of the dioxygen radical coupling to form O 2 is as low as 1.17 eV (Figure S19a, Table S4), which further suggests that the OER over the RuCoO x might proceed with the DOM reaction pathway.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations